Tapering and peaking for biathlon competition - Mujika, I. (Journal of Biathlon Coaching, 2025)
A properly periodized training program should help biathletes increase their physical, technical and psychological abilities to the highest possible levels, and ensure that the maximal performance is attained at the right time of the season (i.e., at each point of a major competition). In many endurance sports and competitive events, such top performances are often associated with a marked reduction in the training load undertaken by the athletes during the days before the competition. Such a reduction is widely known as a taper, and it allows athletes to capitalize on the intensive work performed in the previous training phases (Mujika et al. 1996).